Multi-Disease Segmentation of Gliomas and White Matter Hyperintensities in the BraTS Data Using a 3D Convolutional Neural Network - Rudie, Jeffrey D.; Weiss, David A.; Saluja, Rachit; Rauschecker, Andreas M.; Wang, Jiancong; Sugrue, Leo; Bakas, Spyridon; Colby, John B. (Frontiers in Computational Neuroscience, 2019)
An important challenge in segmenting real-world biomedical imaging data is the presence of multiple disease processes within individual subjects. Most adults above age 60 exhibit a variable degree of small vessel ischemic disease, as well as chronic infarcts, which will manifest as white matter hyperintensities (WMH) on brain MRIs. Subjects diagnosed with gliomas will also typically exhibit some degree of abnormal T2 signal due to WMH, rather than just due to tumor. We sought to develop a fully-automated algorithm to distinguish and quantify these distinct disease processes within individual subjects’ brain MRIs. To address this multi-disease problem, we trained a 3D U-Net to distinguish between abnormal signal arising from tumors vs WMH in the 3D multi-parametric MRI (mpMRI, i.e., native T1-weighted, T1-post-contrast, T2, T2-FLAIR) scans of the International Brain Tumor Segmentation (BraTS) 2018 dataset (ntraining=285, nvalidation=66). Our trained neuroradiologist manually annotated WMH on the BraTS training subjects, finding that 69% of subjects had WMH. Our 3D U-Net model had a 4-channel 3D input patch (80x80x80) from mpMRI, four encoding and decoding layers, and an output of either four (background, active tumor (AT), necrotic core (NCR), peritumoral edematous/infiltrated tissue (ED)) or five classes (adding WMH as the fifth class). For both the four- and five-class output models, the median Dice for whole tumor (WT) extent (i.e., union of AT, ED, NCR) was 0.92 in both training and validation sets. Notably, the five-class model achieved significantly (p=0.002) lower/better Hausdorff distances for WT extent in the training subjects. There was strong positive correlation between manually-segmented and predicted volumes for WT (r=0.96) and WMH (r=0.89). Larger lesion volumes were positively correlated with higher/better Dice scores for WT (r=0.33) and WMH (r=0.34). While the median Dice for WMH was 0.42 across training subjects with WMH, the median Dice was 0.62 for those with at least 5 cm3 of WMH. We anticipate the development of computational algorithms that are able to model multiple diseases within a single subject will be a critical step towards translating and integrating artificial intelligence systems into the heterogeneous real-world clinical workflow.